Dosimetric evaluation of newly developed well-type ionization chamber for use in the calibration of brachytherapy sources - Sathiyan Saminathan; Henry Finlay Godson; Retna Ponmalar; Ravikumar Manickam; James Mazarello (Journal of Medical Physics, 2016)
The well-type ionization chamber has been designed for convenient use in brachytherapy source strength calibration. The chamber has a volume of 240 cm 3 , weight of 2.5 kg, and is open to atmospheric conditions. The well-type ionization chamber dosimetric characteristics such as leakage current, stability, scattering effect, ion collection efficiency, and nominal response with energy were studied. The evaluated dosimetric characteristics of well-type ionization chamber were compared with two other commercially available well-type ionization chambers. The study shows that the newly developed well-type ionization chamber is reliable for air-kerma strength calibration. The results obtained confirm that this chamber can be used for the calibrations of high-dose rate brachytherapy sources.